Influence of Different Phase Angles on Polygon Effect of Long Pitch Conveyor Chain - Guojin Wang; Lin Hong; Yanshu Liang (Jixie chuandong)
The slideway restrained conveyor chain is a new type of chain drive configuration. Reasonable selection of various parameters is conducive to improving the performance of the chain. The conveyor chain of a specific case is taken as the research object, and the variation law of the real-time angular velocity of the driven sprocket is calculated. The size of the polygon effect can be expressed by the displacement difference, and the range of the optimal initial phase angle can be found. The simulation results show that the polygon effect of the chain can be reduced by changing the initial phase angle of the main driven sprocket to increase its stability, which provides a certain design basis for the design of the slideway-constrained chain conveyor system.